PENERAPAN METODE MURAJA’AH DALAM MENINGKATKAN HAFALAN AL-QUR’AN SISWA KELAS III DI SDIT AL-MISHBAH SUMOBITO JOMBANG - Eko Hadi Wardoyo; Zainul Abidin; Susiat Minarsih (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2023)
The aim of this research is to examine the application of the Muraja’ah Method in improving the memorization of the Al-Qur'an for Class III students at SDIT Al-Mishbah Sumobito Jombang. The research method used is descriptive qualitative research. Data sources were obtained from Person, Place, and Paper obtained from the field. The data collection technique uses observation, in-depth interviews and documentation. The data analysis technique uses qualitative descriptive analysis using three Miles and Huberman style flows, namely data reduction, data presentation and conclusion drawing or verification. The results of the research show that by applying the muraja’ah method in memorizing the Al-Qur'an at SDIT Al-Mishbah Sumobito Jombang, students have been able to achieve the memorization targets that have been programmed at school, students are able to memorize the Al-Qur'an well, correctly according to makhraj and recitation. With the muraja’ah method, students are able to speed up their memorization compared to without muraja’ah, besides that, students' memorization becomes stronger, whether old memorization or new memorization.